2021
DOI: 10.31234/osf.io/xh4kg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Moral Dynamics: Grounding Moral Judgment in Intuitive Physics and Intuitive Psychology

Abstract: When holding others morally responsible, we care about what they did, and what they thought. Traditionally, research in moral psychology has relied on vignette studies, in which a protagonist's actions and thoughts are explicitly communicated. While this research has revealed what variables are important for moral judgment, such as actions and intentions, it is limited in providing a more detailed understanding of exactly how these variables affect moral judgment. Using dynamic visual stimuli that allow for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The physics engine that the CSM uses is such a probabilistic program, but the approach is much more general. For example, probabilistic programs have been used to explain people’s inferences about the interactions of social agents as well (Baker et al, 2017, 2009; Evans et al, 2017; Gerstenberg & Tenenbaum, 2017; Jara-Ettinger et al, 2016; Sosa et al, 2021; Stuhlmüller & Goodman, 2014; Ullman et al, 2009; Zhi-Xuan et al, 2020). Inference in probabilistic programs often takes the form of running simulations.…”
Section: Discussionmentioning
confidence: 99%
“…The physics engine that the CSM uses is such a probabilistic program, but the approach is much more general. For example, probabilistic programs have been used to explain people’s inferences about the interactions of social agents as well (Baker et al, 2017, 2009; Evans et al, 2017; Gerstenberg & Tenenbaum, 2017; Jara-Ettinger et al, 2016; Sosa et al, 2021; Stuhlmüller & Goodman, 2014; Ullman et al, 2009; Zhi-Xuan et al, 2020). Inference in probabilistic programs often takes the form of running simulations.…”
Section: Discussionmentioning
confidence: 99%
“…a busy craftsperson might have less time to work on the job). Much work has shown that various factors about an agent can affect responsibility attributions in general, including consideration of the agent's mental states like their intentions (Cushman, 2008;Lagnado & Channon, 2008;Lombrozo, 2010) and reasons (Cushman, 2008), their skills and capacities (Gerstenberg, Ejova, & Lagnado, 2011;Malle et al, 2014;Weiner & Kukla, 1970), and their character more generally (Gerstenberg et al, 2018;Langenhoff et al, 2021;Sosa et al, 2021;Uhlmann, Pizarro, & Diermeier, 2015;Zhao & Kushnir, 2022). The various inferences that are licensed based on the information about the contributor's prior availability were reflected in the individual model fits -some participants assigned more responsibility to busy contributors, some assigned less responsibility, and for some it made no difference.…”
Section: Discussionmentioning
confidence: 99%
“…Responsibility and value. One way that people may allocate responsibility in groups is in proportion to the amount of some units put into achieving the outcome, such as points scored, time spent, or effort exerted (Gerstenberg & Lagnado, 2010Koskuba, Gerstenberg, Gordon, Lagnado, & Schlottmann, 2018;Sosa, Ullman, Tenenbaum, Gershman, & Gerstenberg, 2021;Xiang, Vélez, & Gershman, 2022). This is especially intuitive for collaborative efforts like playing a team sport or writing a manuscript together.…”
Section: Responsibility and Contributionmentioning
confidence: 99%